ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN KONSUMEN TERHADAP TELUR AYAM RAS DI KOTA LANGSA - Rana Raihanah; Supristiwendi, Supristiwendi; Muhammad Jamil (Bajang Institute, 2024)
The aim of this research is to analyze the influence of the price of purebred chicken eggs, consumer income, number of family members, consumer tastes, and the price of duck eggs on the demand for purebred chicken eggs in Langsa City. The research uses a survey method. This research is based on the research objective, namely using a causal research design. Causal research is research that aims to test a hypothesis about the influence of one or several independent variables on the dependent variable. The sampling technique used in this research was accidental sampling with a sample size of 50 consumers of purebred chicken eggs. The results of the study obtained the linear regression equation as follows: Y = -128.018 + 0.02X1 + 0.000005422X2 + 1.955X3 + 14.065X4 + 0.015X5. The adjusted R2 value of 0.506 means that the price factor for broiler eggs, consumer income, the number of family dependents, consumer tastes, and the price of duck eggs affect the demand for purebred chicken eggs in Langsa City by 50.6%. The remaining 49.4% is influenced by other factors that are not included in this research model. The results of the F test simultaneously show that the price of broiler eggs, consumer income, the number of family dependents, consumer tastes, and the price of duck eggs affect the demand for purebred chicken eggs in Langsa City. The results t separately of consumer income, consumer tastes, and duck egg prices affect the demand for purebred chicken eggs in Langsa City. The t results separately for the price of broiler chicken eggs and the number of family dependents have no effect on the demand for purebred chicken eggs in Langsa City